Pittfalls of MRI measurement of white matter perfusion based on arterial spin labeling - Peter van Gelderen; Jacco A. de Zwart; J.H. Duyn (2008)
Abstract Although arterial spin labeling (ASL) MRI has been successfully applied to measure gray matter (GM) perfusion in vivo, accurate detection of white matter (WM) perfusion has proven difficult. Reported literature values are not consistent with each other or with perfusion measured with other modalities. In this work, the cause of these inconsistencies is investigated. The results suggest that WM perfusion values are substantially affected by the limited image resolution and by signal losses caused by the long transit times in WM, which significantly affect the label. From gadolinium diethylenetriamine pentaacetic acid (Gd‐DTPA) bolus‐tracking experiments ( N = 6), it is estimated that the transit time can be several seconds long in deep WM. Furthermore, simulations show that even at a spatial resolution of 7 μl voxel size, contamination by the GM signals can exceed 40% of the actual WM signal. From 10‐min long flow‐sensitive alternating inversion recovery ASL (FAIR‐ASL) measurements at 3T in normal subjects ( N = 7), using highly sensitive detectors, it is shown that single‐voxel (7 μl) deep WM perfusion values have an signal‐to‐noise ratio (SNR) less than 1. The poor sensitivity and heterogeneous transit time limit the applicability of ASL for measurement of perfusion in WM. Magn Reson Med 59:788–795, 2008. © 2008 Wiley‐Liss, Inc.